The Teacher as a Shepherd: A Philosophical Metaphor for Transformative Christian Education in Indonesia - Bakhoh Jatmiko; Juniriang Zendrato (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
This study addressed the gap in understanding the philosophical foundations of Christian education among teachers in Indonesia, emphasizing the need for a transformative approach to teaching. The research aimed to construct the metaphor of “the teacher as a shepherd” to provide a philosophical framework for Christian education in Indonesia. Employing a qualitative, literature-based methodology, the study analyzed biblical texts, educational theories, and prior research on metaphors in education. The findings highlighted 1) the importance of a philosophical foundation in Christian education; 2) the metaphor of the teacher as a shepherd; 3) roles of the Christian teacher as a shepherd; 4) essential qualities of a shepherd-teacher, and 5) transformative learning as the oal. the significance of metaphors in shaping teachers' professional identity and guiding their pedagogical practices. Specifically, the metaphor of a shepherd encapsulates roles such as guiding, protecting, nurturing, and fostering transformative experiences for students. This metaphor aligns with biblical-theological principles and offers a culturally relevant framework for Indonesian Christian educators. The study concluded that adopting the